Impact of harmonization of collection tubes on Alzheimer's disease diagnosis. (25th October 2013) - Lehmann, Sylvain; Schraen, Susanna; Quadrio, Isabelle; Paquet, Claire; Bombois, Stéphanie; Delaby, Constance; Dorey, Aline; Dumurgier, Julien; Hirtz, Christophe; Krolak‐Salmon, Pierre; Laplanche, Jean‐Louis; Moreaud, Olivier; et al.
Abstract: Objective: The objective of this study was to analyze differences in biomarker outcomes before and after harmonization of cerebrospinal fluid (CSF) collection tubes in Alzheimer's disease (AD) diagnosis. Methods: We analyzed data from French memory centers that switched from different CSF collection tubes to a common one. A total of 1966 patients were included in the study. CSF concentrations of β‐amyloid 1–42 (Aβ42), total tau, and phosphorylated tau (p‐tau181) were measured in each center using the same commercial enzyme‐linked immunoabsorbent assay (ELISA) kits. The diagnostic value of CSF biomarkers according to the type of tube used was then assessed using different cutoffs. Results: The predictive value of Aβ42 was highly affected by the type of collection tube used. The optimal cutoff value for p‐tau181 appeared not to be affected by the type of collection tube whereas that of total tau was slightly changed. New optimal cutoff values were then computed. Conclusions: In a routine clinical environment, the selection of the collection tube and biomarker cutoff value makes a major difference in AD biological diagnosis. The use of a common collection tube among different centers will reduce the risk of misdiagnosis and incorrect patient stratification.